Prostate-Specific Membrane Antigen–Directed Therapy for Metastatic Castration-Resistant Prostate Cancer. Issue 5 (September 2016) - Teo, Min Yuen; Morris, Michael J.
Abstract : Abstract: Prostate-specific membrane antigen (PSMA) is highly expressed on both benign and malignant prostatic tissue. Prostate-specific membrane antigen–directed therapy is conceptually promising, with a potential to additionally serve as a theranostic model in management of advanced prostate cancer. To date, various approaches have been devised and tested, including radiolabeled PSMA antibodies and inhibitor and antibody-drug conjugates. However, development and progress have faced challenges in determining the optimal combination of payload, PSMA-binding moiety, and linker technology. We review the available clinical data to date in PSMA-directed therapies and discuss the challenges faced.